INNOVATIVE APPROACHES TO INTEGRATING TECHNOLOGY IN ENGLISH LANGUAGE LEARNING: ISLAMIC INSTITUTE - Komari Komari; Rosi Fitriyanti Sumedi, Emon Paranoan (International Journal of Teaching and Learning, 2024)
This case study delves into the innovative integration of technology within the English language learning curriculum at Islamic Institute. Employing a mixed- methods approach encompassing surveys, interviews, and observations, the research investigates the diverse pedagogical strategies and the efficacy of technology in fostering language proficiency. The findings unveil a multifaceted landscape where instructors leverage various technological tools, from interactive whiteboards to educational software applications, to create dynamic and engaging learning experiences. Through a fusion of traditional teaching methods with innovative technological resources, educators at the institute strive to cater to students' diverse learning needs and preferences, promoting active participation and autonomy in the learning process. Despite the evident benefits, the study highlights various challenges associated with technology integration, including access barriers and technical limitations. These hurdles underscore the need for tailored interventions and support mechanisms to ensure equitable access to technology-enhanced learning opportunities for all students. Moreover, the findings underscore the transformative potential of technology in promoting inclusive and interactive learning environments that foster language proficiency and prepare students for success in an increasingly digital world. This study contributes valuable insights to the broader discourse on effective pedagogical practices in language education through a nuanced exploration of technology integration in English language learning